A national health impact assessment of achieving tree canopy goals in US urban areas - Michelle C. Kondo; Tamara Iungman; Evelise Pereira Barboza; Dexter H. Locke; Ray Yeager; Dustin Fry; Ava-Clare Steed; Marcia Pescador Jiménez; David Rojas-Rueda; Mark Nieuwenhuijsen (Environmental Research, 2026)

Health burden of transportation noise in the United States: a national assessment with equity analysis - David Rojas-Rueda (Environmental Research, 2026)

Human capital in the context of environmental health risks: A narrative review - David Rojas-Rueda; Marie Larson; Khaled Mahdi; Salem Albalawi; Eman Alasfoor; Reem Alsukait; Volkan Cetinkaya; Shwetlena Sabarwal; Johannes Koettel; Christopher H. Herbst (Environmental Science & Policy, 2026)

Health impacts of bus rapid transit systems in seven cities worldwide - David Rojas-Rueda; Georgette A. Aramouni (Environmental Research, 2026)

Green hospitals: maximizing health and climate benefits globally - David Rojas-Rueda (Science of The Total Environment, 2025)

Environmental justice mapping tools in the United States: A review of national and state tools - Hannah Besse; David Rojas-Rueda (Science of The Total Environment, 2025)

Parking and Public Health - Michael D. Garber; Tarik Benmarhnia; Jacob Mason; Emily Morales‐Zamora; David Rojas-Rueda (Current Environmental Health Reports, 2024)
Purpose of Review Parking is a ubiquitous feature of the built environment, but its implications for public health are under-examined. This narrative review synthesizes literature to describe pathways through which parking may affect population health. Recent Findings We begin by contextualizing the issue, outlining key terminology, the sheer scale of land dedicated to parking, and the historical factors that led to this dominant land use. Next, we delineate four pathways linking parking with public health: 1) Promoting driving and car dependency, affecting air pollution, greenhouse-gas emissions, physical activity, traffic-related injuries and fatalities, and accessibility; 2) Creating impervious surfaces, with consequences for urban heat, flooding, water pollution, and green space; 3) Affecting housing affordability and associated health outcomes of this social determinant; and 4) Design, construction, and maintenance, the health impacts of which include on-street parking’s positive and negative impacts on safety for all roadway users, air-quality effects of parking’s construction and maintenance, and the potential for green parking lots to mitigate some health consequences of impervious surfaces. Summary While evidence supports each pathway, additional empirical research is needed to evaluate impacts of parking on public-health outcomes. As a dominant feature of the built environment with many health implications, parking warrants attention by public-health research and practice.

Addressing Health Equity in the Context of Carbon Capture, Utilization, and Sequestration Technologies - David Rojas-Rueda; Kelly McAuliffe; Emily Morales-Zamora (Current Environmental Health Reports, 2024)

Health implications of urban tree canopy policy scenarios in Denver and Phoenix: A quantitative health impact assessment - Daniel Dean; Michael D. Garber; G. Brooke Anderson; David Rojas-Rueda (Environmental Research, 2024)

Who benefits from green spaces? Surrounding greenness and incidence of cardiovascular disease in a population-based electronic medical records cohort in Madrid - Pedro Gullón; Mario Fontán-Vela; Julia Díez; Mark Nieuwenhuijsen; David Rojas-Rueda; Francisco Escobar; Manuel Franco (International Journal of Hygiene and Environmental Health, 2023)

Equitable Urban Planning: Harnessing the Power of Comprehensive Plans - David Rojas-Rueda; Emily Morales-Zamora (Current Environmental Health Reports, 2023)

Built Environment, Transport, and COVID-19: a Review - David Rojas-Rueda; Emily Morales-Zamora (Current Environmental Health Reports, 2021)